Pengetahuan Bantuan Hidup Dasar dengan Pelaksanaan pada Perawat (Journal of Telenursing (JOTING), 2024)
This study aims to determine the relationship between knowledge and the implementation of essential life support in inpatient nurses at the Hospital. The quantitative research method was cross-sectional, with a sample of 68 nurses in the inpatient room of the hospital. The results of this study obtained a p-Value of 0.032 =